2020
DOI: 10.1089/ten.tea.2020.0018
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Response to a Bioactive Biphasic Biomaterial in the Femoral Neck of Osteoporotic Rats

Abstract: Osteoporosis often leads to fragility fractures of the hip resulting in impaired quality of life and increased mortality. Augmenting the proximal femur could be an attractive option for prevention of fracture or fixation device failure. We describe a tissue engineering based strategy to enhance long-term bone formation in the femoral neck of osteoporotic rats by locally delivering bioactive molecules; bone morphogenic protein-2 (rhBMP-2) and zoledronic acid (ZA) using a calcium sulphate/hydroxyapatite (CaS/HA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…[26,27] Recently, Kok et al [15] reported that fixation could be improved with utilization of calcium sulfate/hydroxyapatite (CaS/HA) biomaterial injected through cannulated hip screws, increasing the pullout strength on synthetic bone models. Another recent in vivo study by Raina et al [28] found that the tissue engineering strategy of using CaS/HA ceramic biomaterial to locally deliver zoledronic acid (ZA) with or without recombinant human bone morphogenic protein-2 in femoral necks of osteoporotic rats had potential to regenerate cancellous bone in Nonetheless, there are several limitations to our study. Despite enrolling the same number of consecutive patients in each center and demographics, fracture and mortality rates being similar, as well as distribution of patients in different FAME categories, we consider selection bias and heterogeneity of patients as limitations related to the retrospective design.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…[26,27] Recently, Kok et al [15] reported that fixation could be improved with utilization of calcium sulfate/hydroxyapatite (CaS/HA) biomaterial injected through cannulated hip screws, increasing the pullout strength on synthetic bone models. Another recent in vivo study by Raina et al [28] found that the tissue engineering strategy of using CaS/HA ceramic biomaterial to locally deliver zoledronic acid (ZA) with or without recombinant human bone morphogenic protein-2 in femoral necks of osteoporotic rats had potential to regenerate cancellous bone in Nonetheless, there are several limitations to our study. Despite enrolling the same number of consecutive patients in each center and demographics, fracture and mortality rates being similar, as well as distribution of patients in different FAME categories, we consider selection bias and heterogeneity of patients as limitations related to the retrospective design.…”
Section: Discussionmentioning
confidence: 89%
“…With further developments in this field, modifications to the FAME index can be done to increase its ability to identify suitable patients for inclusion in registry-nested RCT trials. [27,28] In conclusion, the FAME index appears to be a useful stratification tool for allocating patients in a RCT studying augmentation of hip fragility fractures. Further well-designed, large-scale, prospective RCTs are warranted to draw more reliable conclusions on this subject.…”
Section: Discussionmentioning
confidence: 91%
“…For these reasons, several groups have exploited the loading of osteoporotic bones in a constrained configuration. 8,11,1416,22 These have ranged from loading the distal femur epiphysis in osteopenic rats, 23 to axial loading of the femoral neck of osteoporotic rats 9 and to measurement of the biomechanical properties of mouse femoral neck in a constrained axial load model. 8,11,14,15,18 There are also reports of modified biomechanical properties in the femoral neck following in vivo treatment with exercise or Vitamin D deficiency when loaded to failure.…”
Section: Discussionmentioning
confidence: 99%
“…9,11,14,15 They have also been used to evaluate whether biomaterial implants improve defect healing in the rat femoral neck, with increases in bone volume in the absence of any changes in biomechanical parameters reported. 16,17 Thus, it appears that constrained loading methods allow for precise and reproducible measurement of murine femoral neck mechanical properties, but to-date these have remained somewhat limited in their assessment of the effects of ovariectomy. 8,9,18…”
Section: Introductionmentioning
confidence: 99%
“…Radioactive active ZA was measured in the synthetic HA particles as well as in the contralateral femur when the animals were euthanized at six months. 29 It appears that bisphosphonates not only bind to the mineral, but remain bound in the bone for an extended period, potentially for years. The drug is eventually released in small amounts by osteoclast activity, only to be recirculated and rebound into vesicles that precipitate into new calcium phosphate mineral.…”
Section: Hydroxyapatite As a Drug-seeking Moietymentioning
confidence: 99%